Draft Annual Plan 1987-88 Volume-I Notes Government of Andhra Pradesh - Planning Commission (Planning Commission, 1986)
As we march into the middle year of the Seventh Five Year Plan, Andhra Pradesh Government have reassessed the entire gamut of plan implementation so far and reaffirmed the directions in which the plan would be implemented in the remaining years of the Seventh Five Year Plan. At the commencement of the preparation of this Annual Plan, the Chief Minister of Andhra Pradesh had addressed a letter to all Secretaries to Government of Andhra Pradesh stating that the poor, deprived and weaker sections of the society, particularly members of the Scheduled Tribes, Scheduled Castes and Backward Classes, have not received their due share even after decades of planned developmental effort.
Government of Andhra Pradesh, Finance and Planning (PLG. Wing) Department
Government of Andhra Pradesh, Finance and Planning (PLG. Wing) Department